Analisis Efektifitas Media Pembelajaran Phypox Berbasis Android Pada Pembelajaran Fisika SMA Pada Materi Tumbukan - I Ketut Mahardika; Subiki Subiki; Silvia Ainur Rohma; Eryna Dwicahyaning Krisnawanto; Muhammad Najih Hamdi (Universitas PGRI Palembang, 2022)
Communication relations between teachers and students will be better and more efficient. In learning physics, each high school has limited practical tools. This underlies the research on the effectiveness of learning media for the Android-based phypox application. Media in the learning process has a role as teaching aids and learning resources that are used by students independently. Environmental-based learning includes the use of the environment with the object observation process. The environmental-based learning media in this study used android to study collision physics material and experimental results used android to access the phypox application that could be used for collision materials. The method used is an experimental method with a quasi-experimental design with two groups only posttest, namely two classes that are compared through a posttest. The purpose of this study is how effective the use of phypox learning media on collision material is. The data was processed through a descriptive test on SPSS obtained from the posttest. Followed by hypothesis testing to determine the effectiveness of Android-based phypox learning media on collision material. The experimental results showed that this media was effective as indicated by the results of the Independent T-Test test with less than 0.95. So that the experimental class activities can answer more posttest questions than the control class.